PENGGUNAAN STRATEGI GENIUS LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN IKATAN KIMIA DI KELAS X MIA SMA NEGERI 4 PEKANBARU - Dessy Lusyana Yustin; Radjawaly Usman Rery; Herdini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research on the use of Genius Learning strategy to know the increase of student achievement on the topic of the chemical bonds in class X MIA SMAN 4 Pekanbaru. This type of research is pre-experiment research design with one group pretest and posttest design. Time of data retrieval from the date October 28th – November 20 th 2016. The sample was selected from the five existing classes, obtained class X Science 4. Data analysis technique used is paired t-test. Based on analysis of the data obtained tcount> ttable is 46.22>1.69, it is mean that the use of Genius Learning strategy can improved students achievement on the topic of the chemical bonds in class X MIA SMAN 4 Pekanbaru. Key Words : Genius learning, Learning Achievement, Chemical Bonds